PROBLEMS AND DIFFICULTIES ENCOUNTERED BY FIRST YEAR MBBS STUDENTS IN LEARNING MEDICAL ANATOMY AND SOME OF ITS SOLUTIONS- A FEEDBACK STUDY. - DR SUDAKSHINA CHAKRABARTI; DR S VIJAYLAKSHMI; DR GUNAPRIYA RAGHUNATH (International Journal of Pharma and Bio Sciences, 2017)
The first year MBBS students as they walk into the medical colleges face multiple challenges in the first few months of their course. The subject of medical Anatomy and its subdivisions forms a vast portion of their overall curriculum in first year MBBS with maximum teaching hours. Students face disinterest, lack of understanding, inability to recall andare many a times unable to cope up with the demand of this subject. This study was undertaken to address the problems of students of 1st MBBS in learning Anatomy, methods to rectify these problems and assessment methods and interval as preferred by students. The objectives of the study were to detect the problems faced by students of MBBS first year in learning Anatomy and view of students to proposed methods of rectification. Toanalyze the students view regarding assessment methods and interval in Anatomy. A study was conducted on 132 MBBS studentsstudying in Saveetha Medical College Chennai on completion of firstMBBS exams by means of structured questionnaire distributed to them. Students were exposed to regular teaching methods as suggested by Medical Council Of India Regulations in department of Anatomy and feedback of students regarding problems faced in learning Anatomy and their views regarding proposed rectification methods were obtained. The feedback of students on assessment methods and interval was also obtained. The results were analyzed. Students faced problems in learning histology and this was because they were unable to identify slides. They also faced problems in understanding embryology. The assessment methods preferred by them was written test for theory at end of each region. To rectify their problems they felt more active learning methods like quiz, students seminars, and more frequent revisions to be integrated in the curriculum of Anatomy. This study thus evaluates the students’ opinion regarding Anatomy and its subdivisions. Thus it calls for a better planning of the curriculum, assessment techniques, revision schedule, etc to bring about a more effective and apprehensive teaching and learning of Anatomy.